Von Willebrand Activity of Low Molecular Weight Human Factor VIII Increases by Binding to Gold Granules - Furlan, Miha; Perret, Beat A; Beck, Eugene A (Thrombosis and Haemostasis, 1981)
Human factor VIII/von Willebrand protein is a population of multimers which vary in size but contain apparently identical subunits. Large-molecular-weight forms possess higher ristocetin cofactor/von Willebrand activity than the native smaller oligomers. Disulfide reduction of large factor VIII multimers results in progressively decreasing molecular size and a loss of ristocetin cofactor activity. Small molecular forms of factor VIII were adsorbed onto gold granules (average diameter 20-30 nm) and thereby increased their ristocetin cofactor activity. The amount of adsorbed material and the extent of activation were dependent on the pH of the colloid suspension. The maximum recovery of von Willebrand activity was observed at pH 4.75. Aggregation of fixed human platelets by factor VIII-coated gold particles was dependent on ristocetin concentration and was not competitively inhibited by unbound low-molecular-weight factor VIII. These results suggest that the subunits of the native small factor VIII species possess potential binding affinity for platelet receptors, which is manifested following formation of large factor VIII polymers. We conclude that an optimal size of remarkably high molecular weight is required for efficient aggregation of platelets by factor VIII as occurs during the primary phase of hemostasis.
Keywords: Factor VIII/von Willebrand factor; Platelet aggregation; Gold granules